2018
DOI: 10.1016/j.tsep.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Bubble-pump-driven LiBr-H2O and LiCl-H2O absorption air-conditioning systems

Abstract: A thermally-driven bubble pump, powered by solar or waste heat energy, is a simple and efficient technique for lifting a liquid from lower to higher levels, after which it can flow by gravity. In this study, solar thermal driven pumps were incorporated in the solar collector as well as in the refrigerant cycle to provide a design of an airconditioning system for a residential home that is independent of grid electricity. The crystallization challenge, low pressure, and low efficiency are the main downsides of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Thermal bubble technology [ 10 , 11 , 12 ] has been used in many research experiments and industries [ 13 ] since it was firstly applied in the inkjet [ 14 , 15 , 16 ]. Specially, the thermal-bubble-based microvalves and micropump have played quite important roles in different fields, such as aerospace [ 17 ], biomedicine [ 18 , 19 ], and chemistry [ 20 , 21 ]. Currently, resistance heating [ 10 , 22 ] is the most conventional and simplest method in bubble generation.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal bubble technology [ 10 , 11 , 12 ] has been used in many research experiments and industries [ 13 ] since it was firstly applied in the inkjet [ 14 , 15 , 16 ]. Specially, the thermal-bubble-based microvalves and micropump have played quite important roles in different fields, such as aerospace [ 17 ], biomedicine [ 18 , 19 ], and chemistry [ 20 , 21 ]. Currently, resistance heating [ 10 , 22 ] is the most conventional and simplest method in bubble generation.…”
Section: Introductionmentioning
confidence: 99%
“…Papers that studied bubble pumps that used in Einstein refrigeration system or other vapour absorption refrigeration systems are relatively common compared to the investigation of Einstein refrigeration system alone. Researchers from University of Windsor, Canada modelled and analysed the performance of bubble pump for a vapour absorption refrigeration system [17][18][19]. Lin et al, [20] from Institute of Refrigeration Technology, China, studied the bubble pump with the configuration of multiple tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the authors reported that the LiCl-H 2 O mixture presented a better performance than the LiBr-H 2 O mixture. Aman et al [21] theoretically analyzed the performance of a bubble-pump-driven LiCl-H 2 O and LiBr-H 2 O absorption air conditioning systems. The authors reported that, under the same operating conditions, the system operating with the LiCl-H 2 O achieved higher coefficients of performance and cooling capacities than those obtained with the LiBr-H 2 O pair.…”
Section: Introductionmentioning
confidence: 99%